Qualidade de vida, suporte social e fragilidade em idosos atendidos em centro de referência de assistência social - Cesário, Larissa Cayla (Universidade Federal de São Carlos, 2021)
Aging in concomitance with frailty can overload health and social assistance systems that target elderly people. Assessing them in the context of social vulnerability will contribute data for decision making and improvement of actions and proposals of the equipment that serve these individuals. The main objective of the study was to analyze the fragility of elderly people living in neighborhoods with social vulnerability and registered in CRAS in relation to life quality, cognition, health perception, support, family and social relationships. The secondary objective was to analyze the burden of family caregivers and limitations/difficulties in providing care for the elderly. This is a transversal study, observational and analytical, using the quantitative and qualitative method of investigation. The following techniques were applied: observation, semi-structured interview and use of assessment and screening instruments for biopsychosocial conditions of elderly people and family caregivers. The instruments applied to elderly participants were the Edmonton Frail Scale to assess frailty, WHOQOL – bref and WHOQOL-old to verify quality of life, The Montreal Cognitive Assesstment to track cognitive impairment, Genogram, Ecomap and Medical Outcomes Study to verify support and social support network. The instruments applied to caregiving participants were the Zarit Burden Interview to assess the caregiver's burden, Subjective Fragility to verify the frailty condition of the elderly person being cared for and three open questions about the care process. The data were analyzed using descriptive statistics with the creation of frequency tables, position and dispersion measures for the quantitative. Mann-Whitney and Kruskal-Wallis tests or Fisher's exact test were used for comparison between groups to compare categorical variables. Qualitative data were analyzed using a content analysis method. The study included 70 elderly people registered in CRAS and 18 family caregivers of elderly people registered in CRAS. Most elderly participants (n = 70) were women (87.14%), with a mean age of 72.57 years (sd = 7.52), white (51.42%), catholic (60%), widowed (45.72%), retired (51.42%), with incomplete elementary schooling (64.29%). As for fragility, 37.20% were fragile at some level. Of the frail elderly, 47.05% had an indication of cognitive decline. There was a strong negative correlation between frailty and quality of life in the physical domain (-0.667; p <0.001) and moderate in the psychological domain (-0.586; p <0.001). In the qualitative analyzes, three categories emerged: family arrangements and relationships of elderly people, welcoming and mourning relationships and social support. Most of the participants in family caregivers (n = 18) were women (88.8%), with a mean age of 59 years (sd = 12.13), married (77.7%), without individual income (72.2 %) and unemployed (72.2). As for the frailty self-perceived by the elderly person's caregiver, 88.8% of the elderly cared for are considered fragile. Regarding the assessed overload, 66.6% had some overload. As for reports of difficulties in care, 77.7% of respondents said they felt some difficulty in caring. In the qualitative analyzes carried out from the report of family caregivers, 2 categories emerged: forms of care and difficulties in the care process. The results demonstrate that fragile elderly people have a worse quality of life, in the physical and psychological domain and need assistance to perform activities of daily living. Family caregivers were overwhelmed and had several difficulties in their care tasks. Qualitative data point to influences from the family nucleus on the quality of life of elderly people, which may influence positively or negatively. The tensions identified from the analysis of reports from elderly participants and caregivers were related to the needs arising from sociodemographic and health conditions and types of support available to meet the different demands and may contribute to the development, implementation and evaluation of public policies for this populational.
Life quality, social support and fragility in older adults attended at social assistance reference center
Keywords: Cuidador Familiar; Assistência Social; Política Pública; Idoso fragilizado; Frail; Family Caregiver; Social Assistance; Public Policy; OUTROS